Revisão do Plano Diretor de Goiânia, 2017-2022: Uma análise na perspectiva da gestão democrática e do direito à cidade - Côrtes, Tiago Martins (2025)
This research explores the complex relationship between the human right to the city and democratic management in the city of Goiânia. A historical review of the urbanization process reveals that contemporary cities, shaped by the logic of capitalism, function as centers of production and consumption, where the commodification of urban space perpetuates social inequalities, concentrating wealth and power in certain areas while marginalizing and excluding others. From this perspective, the study discusses the impacts of capitalism on Brazilian urban development, highlighting how urbanization intensifies social and spatial inequalities. The concept of the right to the city, based on the principles of Henri Lefebvre, is central to this research, emphasizing the need for equity in access to public goods and services, especially for marginalized individuals. In Brazil, urban legislation, founded on the principles of the 1988 Federal Constitution, recognizes the Master Plan as the primary instrument for urban planning and for promoting the social function of the city and property. Democratic management is emphasized as a fundamental principle and a requirement for the validity of the laws establishing master plans, as provided for in the City Statute. The effectiveness of this principle was put to the test during the revision process of Goiânia’s Master Plan, initiated in 2017 and concluded in 2022, which was subject to various criticisms and legal challenges regarding transparency and the exclusion of civil society segments from public hearings. Additionally, several changes introduced in the new version of the Master Plan were found to contradict public interests while favoring corporate and real estate market interests, deepening the tension between collective objectives and economic pressures. Using historical-dialectical materialism as the primary theoretical framework to understand the class struggle shaping urban space, this research aims to analyze the revision process of Goiânia’s Master Plan (2017–2022) from the perspective of democratic management and the right to the city.